Evaluation of the antidiabetic activity of ethyl acetate partition of ekor naga leaves (Rhaphidophora pinnata (L.f) Schott) on male white mice induced by alloxan - Kasmadi, Fathnur Sani; Maimum; Yuliawati; Maharini, Indri; Sari, Vinka Lupita; Hz, Tia Wida Ekaputri; Perkasa, Tengku Arief Buana (Proceedings Academic Universitas Jambi, 2025)
Background: Diabetes mellitus is a condition where blood glucose levels increase due to a decrease in the amount or sensitivity of insulin produced by the body. Previous research has shown that the ethanol extract of Ekor Naga leaves (Rhaphidophora pinnata (L.f.) Schott) has potential as an antidiabetic agent. The extract also contains several secondary metabolic compounds such as flavonoids and phenolics, which are suspected to have antidiabetic potential. Objective: This research aims to investigate the activity of ethyl acetate partitioning of Ekor Naga leaves extract (Rhaphidophora pinnata (L.f.) Schott) in reducing blood sugar levels in diabetic mice. Methods: This research employed a Completely Randomized Design (CRD) method with six treatments: a normal control, a glibenclamide positive control, a Na-CMC negative control, and treatment groups with doses of 125, 250, and 500 mg/kg body weight (BW) of the ethyl acetate partition of ekor naga leaves extract. The observed parameter was the average decrease in blood sugar levels over a 21-day period.Results: The results were analyzed using the one-way ANOVA test, followed by Duncan’s multiple range test. The research showed that the ethyl acetate partition of Ekor Naga leaves can reduce blood sugar levels in mice over 21 days. The results have shown significant improvement in blood sugar levels between treatment groups. The best dose in reducing blood glucose levels was 500 mg/KgBW with a percentage decrease of 58.98%.Conclusion: Ethyl acetate partition of ekor naga leaves has potential as an antidiabetic agent.